Proposed Strategy Formulation and The Implementation for PT. XYZ - Jumar, Jumar; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2012)
Indonesian paint market is one of the fastest growingÂ  markets in the world (CAGR 2009-2011 at 8.3 %) and the market still has huge potency to grow due to the paint consumption per capita (PCP) still low at 2.8 kg/person (world PCP at 6-7 kg/person). On the other side, paint companies currently faced pressure on profit margin due to the more strict competition and increase of the key raw materials price (eg. TiO2 and binder). PT.XYZ, a paint company, has established in Indonesia since 1983. By 2010, its sales just accounted forÂ  2.2 % market share, and just use 48.3 % of its total production capacity. From the external and internal environmental analysis concluded that the main problems (weaknesses) faced by XYZ are the lack of advertising programs that cause low brand awareness of its products, and lack of high skills marketing human resources. The root cause of the problems is the absence of strategic management processes at PT. XYZ.Â The purpose of this research is to propose the strategy formulation and the implementation plan for PT. XYZ to improve its performance through strategic management processes. The corporate strategy generated from SWOT matrix is â€œconcentration (horizontal) growth strategyâ€.Â  The alternative strategies to accomplish the growth strategy are generated through Ansoff matrix that include: market penetration, product development, market expansion to new geographical markets, and enter into industrial paint segment. The proposed business strategy is â€œdifferentiationâ€ strategy via its distribution, products, and services. The functional strategy generated via TOWS matrix are categorized into marketing strategy, operation strategy, financial strategy, and human resources strategy. A Focused Group Discussion (FGD) was performed to evaluate, select, and make prioritizing of the selected strategies. The selected strategies and the priority are: market penetration strategy, product development strategy,Â  and market expansion to other geographical markets.Â The implementation of the selected strategies are through developing integrated programs and actions plan at each functional departments. The marketing programs are focused to increase its product brand awarenessÂ  and increase sales via advertising, sales promotion and more focus in project channels. The operation programs are increase actual production capacity and establish efficient operation. The human resources programs are to provide the HR needed to execute the selected strategies and establish good HR management practicesÂ  at SCI for the long-run program. Then, the financial program is raising external funds and manage funds efficient and effectively. Key words: strategic management, corporate strategy, business strategy, functional strategy, program and action plan